Anti-inflammatory and antioxidant properties of Camellia sinensis L. extract as a potential therapeutic for atopic dermatitis through NF-κB pathway inhibition - Min Jung Kim; Ye Jin Yang; Ga-Yul Min; Ji Woong Heo; Jae Dong Son; Young Zoo You; Hun Hwan Kim; Gon Sup Kim; Hu-Jang Lee; Ju-Hye Yang; Kwang Il Park (Scientific Reports)
Abstract Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by immune dysregulation and excessive cytokine production. This study aimed to explore the potential of Camellia sinensis L. water extract (CSE) as a treatment for AD by the impact of CSE on inflammatory responses in keratinocytes, particularly concerning the production of inflammatory cytokines and the modulation of signaling pathways relevant to AD pathogenesis. CSE was obtained via hot water extraction from Camellia sinensis L. Ultra-high-performance liquid chromatography (UPLC) analyzed catechin and caffeine content. Cell viability was assessed with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), polyphenol and flavonoid content were determined. 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay measured antioxidant activity. Enzyme-Linked Immunosorbent Assay (ELISA), western blotting, and Immunofluorescence (IF) assays examined cytokines, pathways, and protein localization, respectively. Molecular docking assessed compound binding with inflammation-related proteins. UPLC identified six CSE components including epigallocatechin (EGC) epicatechin (EC), caffeine (CF), catechin (C), epigallocatechin gallate (EGCG), and epicatechin gallate (ECG). CSE demonstrated a significant reduction in the production of inflammatory cytokines interleukin (IL)-2 and IL-6 in TNF-α/IFN-γ activated keratinocytes. Treatment with CSE inhibited the mitogen-activated protein kinase (MAPK) pathway, which resulted in decreased phosphorylation of p38, Jun N-terminal kinase (JNK), and extracellular signal-regulated kinase (ERK). Exposure of TNF-α/IFN-γ- stimulated human keratinocytes (HaCaT) cells to CSE resulted in a 200 µg/mL dependent inhibition of p65 and signal transducer and activator of transcription 1 (STAT-1) translocation from the cytosol to the nucleus, as confirmed through immunofluorescence (IF) staining. Molecular docking simulations provided insights into the underlying mechanisms of CSE action, which supported its potential as a therapeutic agent for AD. CSE might be a potential candidate for its therapeutic efficacy for inflammatory skin conditions like AD. Thus, based on this evidence, the authors suggest that CSE should be studied further for its anti-inflammatory activities and topical application in the treatment of AD.